3D numerical wear model for determining the change in surface topography. (2nd November 2018) - Prajapati, Deepak K; Tiwari, Mayank
Abstract: Micropitting and related surface fatigue mechanisms are influenced by the running-in behavior of contacting bodies subjected to rolling/sliding motion. The running-in of contacting surfaces results in significant change in many surface topography parameters, such as mean summit radius, the radius of individual summits, and standard deviation of summit height, which leads to contact pressure, real contact area, and plasticity index. In this work, running-in wear is simulated by developing a 3D numerical wear model. The simulation is performed on 3D rough surfaces having different skewness and kurtosis. It is shown that mean summit radius and radius of the individual summit are strongly influenced and significantly vary during wear process. It is found that a change in contact pressure and plasticity index can be related to a single topography parameter. The objective of this work is to show the topography parameters variation during running-in wear, which is hitherto not discussed elsewhere in detail. The variation with the number of cycles for roughness parameters determined from wear experiment and simulation are compared and a good match is found.